Nonylphenol exposure increases the risk of Hirschsprung’s disease by inducing macrophage M1 polarization - Xuefeng Yang; Chengyan Tang; Daiwei Zhu; Xingrong Xia; Qing Du; Lu Huang; Jianguo Liu; Yuanmei Liu (Ecotoxicology and Environmental Safety)
Nonylphenol (NP), a ubiquitous environmental contaminant used as a surfactant in industrial production and classified as an endocrine disruptor, could interfere hormone secretion and exhibit neurotoxicity in organisms. Hirschsprung’s disease (HSCR), one of the most frequently observed congenital malformations of the digestive system, arises mainly due to the failure of enteric neural crest cells to migrate to the distal colon during embryonic development. However, the effects of NP exposure on HSCR are largely unknown. Herein, we identified the content of NP and expression of lncRNA LINC00294/Inhibin Subunit Beta E (INHBE) axis in clinical samples and evaluated the crucial role of lncRNA LINC00294/INHBE axis in the neurogenic potential of neurons and the neurotoxicity effects of NP in the SH-SY5Y cells and female specific pathogen-free (SPF) rat model. Our results showed that NP concentration and LINC00294 were significantly associated with HSCR occurrence and macrophage polarization in human HSCR specimens. Moreover, NP promoted macrophage M1 polarization. The proliferation and migration were weakened, and apoptosis was heightened by the conditioned medium of NP-treated macrophages in SH-SY5Y cells. Contrarily, LINC00294 overexpression and INHBE knockdown reversed the neurotoxicity effect of NP on SH-SY5Y cells. Furthermore, the neurotoxicity effect of NP was abolished by clodronate liposomes in the rat model. In conclusion, NP could induce macrophage M1 polarization via the LINC00294/INHBE axis and increase the risk of Hirschsprung’s disease. Our findings would provide a foundation for the toxicity study and risk assessments of NP.